2003
DOI: 10.1017/s0022112003004762
|View full text |Cite
|
Sign up to set email alerts
|

The extended GrtlerHmmerlin model for linear instability of three-dimensional incompressible swept attachment-line boundary layer flow

Abstract: A simple extension of the classic Görtler–Hämmerlin (1955) (GH) model, essential for three-dimensional linear instability analysis, is presented. The extended Görtler–Hämmerlin model classifies all three-dimensional disturbances in this flow by means of symmetric and antisymmetric polynomials of the chordwise coordinate. It results in one-dimensional linear eigenvalue problems, a temporal or spatial solution of which, presented herein, is demonstrated to recover results otherwise only accessible to the tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 25 publications
2
52
0
Order By: Relevance
“…Numerical method The results of the BiGlobal instability analysis have been verified by linear and nonlinear three-dimensional DNS monitoring the linear development of the disturbance velocity components associated with the stationary leading global mode. The DNS code is a modification of that of Lundbladh et al (1994) and has also been used by Theofilis et al (2003) in the verification of the polynomial modes of swept Hiemenz flow. It considers a velocity-vorticity formulation of the incompressible continuity and Navier-Stokes equations.…”
Section: Direct Numerical Simulationmentioning
confidence: 99%
“…Numerical method The results of the BiGlobal instability analysis have been verified by linear and nonlinear three-dimensional DNS monitoring the linear development of the disturbance velocity components associated with the stationary leading global mode. The DNS code is a modification of that of Lundbladh et al (1994) and has also been used by Theofilis et al (2003) in the verification of the polynomial modes of swept Hiemenz flow. It considers a velocity-vorticity formulation of the incompressible continuity and Navier-Stokes equations.…”
Section: Direct Numerical Simulationmentioning
confidence: 99%
“…Lin & Malik (1997) went on to analyse by global linear stability theory the effect of streamwise curvature and concluded that it stabilizes the flow, thus offering additional motivation to analyse the stability of plane stagnation flows first. Theofilis et al (2003) also performed global instability analysis and DNS of the incompressible swept Hiemenz flow, fully confirming the existence of the sequence of the global modes predicted by Lin & Malik (1996), and proposed a polynomial model to describe the chordwise dependence of the amplitude functions of these modes. The polynomial model converts the partial differential equation (PDE)-based global linear instability analysis EVP into an ordinary differential equation (ODE)-based one, without loss of physical information in the linear regime.…”
Section: Linear Global Instability Of a Non-orthogonal Incompressiblementioning
confidence: 58%
“…However, instead of embarking upon parametric studies of instability by numerical solution of the partial-derivative EVP or by DNS, the question is addressed next whether it is possible to simplify the full system of equations describing linear stability by a polynomial model analogous with that proposed by Theofilis et al (2003) for the orthogonal case; attention is turned to this issue next.…”
Section: Recovery Of Amplification Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should, however, be stressed that in the present matrix-forming context the issues arising from the splitting formulation of the incompressible equations of motion, where inappropriate use of pressure boundary conditions in the time-integration algorithm may violate mass conservation, are not directly related to the boundary conditions to close the linearized Navier-Stokes system. Pressure compatibility (PC) boundary conditions, derived from the momentum equations and collocated at the wall, have been shown to perform well in classic linear stability analysis [41] and their extension in two spatial dimensions is the natural candidate to provide the sought closure of the system of linearized equations of motion; indeed, these conditions have been used successfully in the global instability analysis of a number of well-studied incompressible flows [35,36,57,63,64].…”
mentioning
confidence: 99%